An annotated checklist of trees and relatives in tropical montane forests from southeast Peru: the importance of continue collecting - Farfan-Rios, William (2015)
The tropical Andes and adjacent Amazon are Earth’s highest biodiversity hotspot. Manu National Park in southeastern Peru encompasses an entire watershed, ranging from Andean highlands to Amazonian lowlands, and is a megadiverse landscape on the Andes to Amazon transition. Here we present an annotated checklist of trees and related species is along an elevation gradient in the Manu Biosphere Reserve that runs from sub-montane forests at 800 m elevation up to the tree line at 3625 m. Based on a network of 21 1-hectare permanent tree plots and botanical explorations, the floristic information is systematized by elevation ranges, geographical distribution and endemism. These preliminary results show 1108 species. Of these, 43% are new records for the region of Cusco, 15 species are new records for the Peruvian flora, 40 species are endemics for Peru, and 30 are potential new species for science. Another 39.7% are identified to genus or family level and remain morphospecies. Additionally, we show altitudinal range expansion for 45.2% of identified species (302 species). These results were found in a transect of plots spanning only 20 km of geographic distance, and are a sample of the high tree diversity in these mountainous ecosystems. The data show how poorly collected and understudied these ecosystems are. Basic floristic studies and collections are imperative for a better understanding of species distribution and function of ecosystems, and the basic biodiversity of the tropical Andes. They will also help to answer a major, unresolved question in modern global ecology of how tropical forests will respond to global climate change.